2009
DOI: 10.1007/s11552-009-9163-1
|View full text |Cite
|
Sign up to set email alerts
|

The Buttazzoni Classification of Distal Radial Fractures in Adults: Interobserver and Intraobserver Reliability

Abstract: Despite the fact that distal radial fracture is the commonest fracture, there is a little evidence-based knowledge about the value of its classification to guide management and predict prognosis. The available classification systems are either complicated or weakly applicable in clinical practice. Older's classification is the most reliable, but does not cover all radial fracture types. We evaluated the interobserver and intraobserver reliability of a new classification system which is a modification of Older'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…It describes the degree of dorsal displacement of the distal fragment, the degree of radial shortening and the degree of comminution of the dorsal cortex close to the fracture, as predictors of fracture instability. A further development of the Older classification is the recently introduced Buttazoni classification 10 , which is simpler and includes comminution of the volar cortex as a predictor of instability. A commonly used classification is the universal AO/OTA system 11 which describes three main types of fractures: (A) extraarticular, (B) partial intraarticular and (C) complete intraarticular, with subgroups within each main type.…”
Section: Fracture Classificationmentioning
confidence: 99%
“…It describes the degree of dorsal displacement of the distal fragment, the degree of radial shortening and the degree of comminution of the dorsal cortex close to the fracture, as predictors of fracture instability. A further development of the Older classification is the recently introduced Buttazoni classification 10 , which is simpler and includes comminution of the volar cortex as a predictor of instability. A commonly used classification is the universal AO/OTA system 11 which describes three main types of fractures: (A) extraarticular, (B) partial intraarticular and (C) complete intraarticular, with subgroups within each main type.…”
Section: Fracture Classificationmentioning
confidence: 99%
“…We found no statistically significant differences in QuickDASH, EQ-5D questionnaire, EQ-5D health status VAS, and pain VAS scores among the Buttazzoni classes. Surgical technique differed among the fracture classes (►Table 7). No B0 and only one B1 fracture were treated surgically.…”
Section: Resultsmentioning
confidence: 99%
“…23 The utility of this system by testing its interobserver reliability and intraobserver reproducibility was previously reported. 7 In a prospective multicenter clinical trial, the ability of the system to predict radiological stability was tested, and revealed that fractures with initially nonacceptable radiographic alignment and cortical comminution were highly unstable. 8 In this study, we aimed to evaluate the effect of dorsal and volar comminution, intra-articular involvement, and initial displacement on clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations